Mental and behavioral health settings: Importance & effectiveness of environmental qualities & features as perceived by staff. (June 2017) - Shepley, Mardelle McCuskey; Watson, Angela; Pitts, Francis; Garrity, Anne; Spelman, Elizabeth; Fronsman, Andrea; Kelkar, Janhawi
Abstract: This paper describes research on the design of behavioral and mental health facilities. Using input from clinical staff, the purpose of the study was four-fold: to develop and test a tool for the evaluation of mental and behavioral health (MBH) facilities, to evaluate the importance and effectiveness of specific environmental qualities and features, to generate design guidelines for MBH facilities, and to make recommendations for future research. A draft version of a tool that was intended to measure the importance and effectiveness of environmental qualities and features in MBH facilities was developed using a multi-methods approach. This survey, the Psychiatric Staff Environmental Design (PSED) tool, was distributed to psychiatric nursing organization members (N = 134). The researchers determined that the PSED was suitable for future research with minor modifications. Other findings included staff support for private patient rooms, staff recognition of the critical role of positive distraction, and the importance of aesthetics. Highlights: Staff evaluated the effectiveness and importance of environmental features in mental and behavioral health environments. Respondents typically supported private rooms, open nurse stations, and the presence of positive distraction. Specific environmental features were noted as being important but absent in most facilities. The Psychiatric Staff Environmental Design (PSED) tool was found to be suitable for use in evaluating facilities. Design guidelines and a research agenda are provided.